Occupational choice of high skilled immigrants in the United States - Barry R. Chiswick; Sarinda Taengnoi (Institute for the Study of Labor (IZA), 2007)
This paper explores the impact of English language proficiency and country of origin on the occupational choice of high-skilled immigrants in the U.S. using the 2000 Census. The findings reveal that high-skilled immigrants with limited proficiency in English, or whose mother tongue is linguistically distant from English, are more likely to be in occupations in which English communication skills are not very important, such as computer and engineering occupations. Moreover, the degree of exposure to English prior to immigration is found to have little influence on selecting occupations in the U.S. The paper also shows that immigrants from some origins with little exposure to English and whose native language is far from English tend to be in some speaking-intensive occupations, in particular social services occupations. These occupations may not require workers to be fluent in English if they mostly provide services to immigrants from their same linguistic background.
Keywords: 330; Migranten; Berufswahl; Sprache; Englisch (Sprache); Hochqualifizierte Arbeitskräfte; USA